Quality of life of Iranian and Afghan pregnant women in rural Iran - Shams, L.; Tajik, M.; Heidari, P.; Nasiri, T.; Mohammadshahi, M. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Pregnancy is a unique experience in a woman’s life, which comes with physiological, metabolic, social, and psychological changes. The combination of these changes along with migration, may reduce the quality of life of pregnant women and mothers. This study aims to determine the quality of life in rural pregnant women. Methods. A cross-sectional study was conducted. Three hundred pregnant Iranian and Afghan women who attended the public health centers in regional Tehran, Iran, were systematically selected and included in the study. Different dimensions of health status were investigated using the standard health-related quality of life questionnaire (SF-26) through interviews. SPSS version 23 was used for data analysis. Results. The psychological health subscale (38.00) in the Iranian pregnant women and the physical health subscale (38.83) in the Afghan pregnant women had the highest scores. The lowest score was in social functioning subscale in both groups (20.59 in Iranian and 21.22 in Afghans). In general, Iranian mothers had lower scores compared to Afghan mothers. There was a relationship between the quality of life of Iranian pregnant women, their level of education and family’s monthly income (P <0.05), and between the quality of life of Afghan pregnant women with the lesser number of pregnancies (P <0.05). Conclusions. In rural Iran, the quality of life score and its subscales is comparably low in both Iranian and Afghan pregnant women. Interventions are needed to improve the quality of life in this vulnerable population.